DAMPAK REKRUTMEN DAN SELEKSI TERHADAP PRODUKTIVITAS PEGAWAI PENGEMBANGAN KAWASAN PEMUKIMAN PROVINSI SUMATERA BARAT - Febriani Febriani; Lenny Hasan (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2019)
The company always expects good performance for employees, because employees are the key to success for the company. In order to get qualified employees, it is necessary to pay attention to the procedures for recruitment and selection. The purpose of the study was to find out how much the impact of recruitment and selection on increasing the work productivity of employees of the Settlement Development Unit of West Sumatra Province. The research method used is quantitative research methods. The population in this study were all employees of the Settlement Development Unit of West Sumatra Province totaling 48 employees. The sampling technique is the total sampling method that is using the entire population as the study sample. The data analysis technique used in this study is multiple linear regression analysis. The results of the research obtained explain that recruitment and selection have a significant impact on the productivity of employees of the Settlement Development Unit of West Sumatra Province.